UNDP's 1996 report on human development in Bangladesh : a pro-poor agenda ; volume 1 overview (Dhaka : UNDP, 1996)
Economics
Keywords: Human development; Human development-Report; Income; Gender gaps; Employment; Health; Pro-poor governance; Empowerment